One-Bit Hard Combination Decision Scheme for Cooperative Spectrum Sensing in Cognitive Radio - Md. Shamim Hossain; Md. Ibrahim Abdullah; Mohammad Alamgir Hossain (International Journal of Informatics and Communication Technology (IJ-ICT), 2015)
In this paper, the performance of 1-bit hard combination decision scheme for cooperative spectrum sensing in Cognitive Radio has been studied to maximize the probability of primary user detection. Energy detector model is used to observe the presence of primary user signal. Simulation result shows that the probability of missed detection is decreasing for both conventional and 1-bit hard combination OR rule with increasing the probability of false alarm correspondingly. It also has demonstrated that 1-bit hard combination decision scheme exhibits comparable performance with the conventional one-bit scheme and thus achieves a good tradeoff between performance and complexity.